Mycobacterium Ulcerans Ulcer: Current Trends in Antimicrobial Management and Reconstructive Surgical Strategies - Bryan Lim; Omar Shadid; Jennifer Novo; Yi Mon; Ishith Seth; Gianluca Marcaccini; Roberto Cuomo; Daniel P. O’Brien; Warren M. Rozen (Life, 2025)
Background: Mycobacterium ulcerans causes Buruli ulcer (BU), a necrotizing skin disease endemic in over 30 countries. Its toxin, mycolactone, drives tissue destruction, and the infection is transmitted via environmental reservoirs or vectors. Disease patterns vary globally, and an improved understanding of their pathogenesis may enhance current antimicrobial and surgical treatments. Methods: A comprehensive literature search from 1901 to 2025 was conducted across major databases to explore antimicrobial and reconstructive surgical strategies for Mycobacterium ulcerans. Search terms included BU, key antibiotics, and surgical interventions. Relevant English-language studies on treatment outcomes were reviewed to summarize evolving management trends and emerging therapeutic approaches. Results and Discussion: This review highlights the importance of early diagnosis and timely antimicrobial therapy in preventing disease progression and limb loss. It reviews WHO-recommended antibiotic regimens and discusses the theoretical risk of drug resistance, although clinical resistance remains rare and unreported in Australia. Surgical interventions in select cases are crucial, with timing being a significant factor in functional outcomes. The review also covers pediatric-specific challenges, including growth preservation and psychosocial support for young patients. Reconstructive options focus on limb salvage and staged reconstructions, with multidisciplinary care essential for optimal outcomes. The paper advocates for RCTs to refine treatment protocols, surgical guidelines, and explore emerging antibiotic therapies such as telacebec. Conclusions: BU remains a global health challenge, requiring early diagnosis, timely antimicrobial therapy, and surgery in selected cases. Future research will refine treatment and reduce long-term impacts.